Implementation of the Single Sign-On (SSO) System in the Integration of ASN Digital Services: A Case Study at the Communication and Informatics Office of Sidoarjo Regency: Implementasi Sistem Single Sign-On (SSO) dalam Integrasi Layanan Digital ASN: Studi pada Diskominfo Kabupaten Sidoarjo - Ilmi Usrotin Choiriyah; Dewi Maftuhah; Ferrin Feriska; Safira Putri Andianti; Beby Rahayu Lailatushiyam; Siti Fatimatul Ilmi (Universitas Muhammadiyah Sidoarjo, 2026)
The development of the Electronic-Based Government System (SPBE) requires the integration of effective, safe, and efficient digital services for the State Civil Apparatus (ASN). One of the problems faced by local governments is the fragmentation of the application system that requires users to perform repeated authentication, thereby reducing work efficiency and increasing information security risks. This study aims to analyze the implementation of the Single Sign-On (SSO) System in the integration of ASN digital services at the Sidoarjo Regency Communication and Information Office. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies during internship activities. The analysis of policy implementation was carried out using the Edward III model which includes aspects of communication, resources, disposition, and bureaucratic structure. The results of the study show that the implementation of SSO is able to increase the efficiency of digital service access, simplify the authentication process, and support the integration of ASN's internal applications. However, the implementation of SSO still faces obstacles in the form of limited digital literacy for some users, data insynchronization between applications, and the need to strengthen information security governance. Therefore, optimizing SSO implementation requires increasing human resource capacity, integrating more integrated databases, and socializing and strengthening internal regulations on an ongoing basis